Integrated mosquitoes repellent with ultrasound and frequency - Ahmad, J. (Institute of Electrical and Electronics Engineers Inc., 2019)
Mosquitoes repellents are already being commercialized, and the technology that is being put in mosquitoes' repellent is increasing. However, the usage of mosquitoes' repellent is not a concern to people as people not always bring mosquitoes repellent anywhere they go. This work presents integrated mosquitoes' repellent with ultrasound and frequency mobile application. It is a mobile application that having features to provide information on infected area with mosquitoes borne disease which link with Perak Health Division website, information of type of species with pictures to acknowledge user on dangerous mosquitoes' species and have the functionality to repel mosquitoes using frequency and ultrasound. Based on the survey that being done, majority of people admitted that they did not frequently bring any mosquitoes repellent when travelling. However, people do aware on mosquitoes borne disease that can cause to death. Therefore, this mobile application is being built to encourage user to use mosquitoes' repellent and to avoid themselves from getting bites by mosquitoes and from mosquitoes borne disease. Â© 2018 IEEE.